Sistem Informasi Pengolahan Data Perkara Perdata Pada Pengadilan Negeri - Wenny Damai Yanti Lumbantoruan (ADA Research Center, 2025)
The development of technology and information through the internet is currently very rapid. Delivering fast, accurate, and relevant information has become a basic need for companies. Technological advances encourage companies to develop solutions to facilitate the delivery of required information. With this Visual Basic-based civil case processing information system, it is hoped that it will facilitate data processing and provide information on processing civil case data at the Balige District Court. In this system, the author designed a civil case data processing system using Visual Basic. XAMPP, MySQL, and Navicat Premium Enterprise serve as database creation tools. The development components mentioned above are expected to simplify the civil case data processing process at the Balige District Court. If the process runs smoothly, the information system will meet expectations.